2018
DOI: 10.1038/s41467-018-03019-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of microRNA-128 promotes cardiomyocyte proliferation and heart regeneration

Abstract: The goal of replenishing the cardiomyocyte (CM) population using regenerative therapies following myocardial infarction (MI) is hampered by the limited regeneration capacity of adult CMs, partially due to their withdrawal from the cell cycle. Here, we show that microRNA-128 (miR-128) is upregulated in CMs during the postnatal switch from proliferation to terminal differentiation. In neonatal mice, cardiac-specific overexpression of miR-128 impairs CM proliferation and cardiac function, while miR-128 deletion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 62 publications
4
109
0
3
Order By: Relevance
“…miRNAs are small endogenous non-coding RNAs composed of [19][20][21][22][23][24] nucleotides that bind to imperfect sequence sites of target mRNA and recruit the RNA-induced silencing complex, causing either degradation or inhibition of protein translation [11]. Generally, one gene can be repressed by multiple miRNAs, and one miRNA may repress multiple target genes, so miRNAs are recognized as important regulators involved in various cellular processes, including differentiation, proliferation, necrosis, and apoptosis [12][13][14]. Recent studies have revealed that multiple miRNAs engage in the regulation of cardiovascular formation, development, and function [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are small endogenous non-coding RNAs composed of [19][20][21][22][23][24] nucleotides that bind to imperfect sequence sites of target mRNA and recruit the RNA-induced silencing complex, causing either degradation or inhibition of protein translation [11]. Generally, one gene can be repressed by multiple miRNAs, and one miRNA may repress multiple target genes, so miRNAs are recognized as important regulators involved in various cellular processes, including differentiation, proliferation, necrosis, and apoptosis [12][13][14]. Recent studies have revealed that multiple miRNAs engage in the regulation of cardiovascular formation, development, and function [14].…”
mentioning
confidence: 99%
“…Generally, one gene can be repressed by multiple miRNAs, and one miRNA may repress multiple target genes, so miRNAs are recognized as important regulators involved in various cellular processes, including differentiation, proliferation, necrosis, and apoptosis [12][13][14]. Recent studies have revealed that multiple miRNAs engage in the regulation of cardiovascular formation, development, and function [14]. For example, miR-21 exerts anti-apoptotic function via targeting Fas ligand or programmed cell death 4 (PDCD4) [15][16][17].…”
mentioning
confidence: 99%
“…Here we refer to heart-specific microRNAs known together as myomiRs (myo = muscle + miR = microRNA), such as mir-128, miR-19a/19b, and other miRNAs with known effects on the heart. They were recently found to play a role in pivotal cell functions involved in cardiac regeneration, i.e., proliferation, reprogramming and differentiation (Huang et al, 2018;Gao et al, 2019).…”
Section: Endogenous Cardiomyocytes Proliferation Induction Mirna Regumentioning
confidence: 99%
“…The correct insertion of the miR-128 cassette and successful removal of the neomycin cassette were confirmed by PCR analysis with the primers listed in Supplementary Table 1." [113] 2) "The C57BL/6J (Jackson) Los Angeles, CA). These mice were originally congenic C57BL/6J (backcrossed for five generations) and were then inbred (cousin matings) over 14 y, during which time they were outbred with C57BL/6JOlaHsd mice on three separate occasions."…”
Section: Explanationmentioning
confidence: 99%